First and Second Best Voting Rules in Committees - Ruth Ben-Yashar; Igal Milchtaich (Bar-Ilan University, Department of Economics, 2003)
A group of people with identical preferences but different abilities in identifying the best alternative (e.g., a jury) takes a vote to decide between two alternatives. The first best voting rule is a weighted voting rule that takes into account the different individual competences, and is therefore not anonymous. Under such a rule, it is rational for group members to vote informatively, i.e., according to their private information. The use of any (non-trivial) anonymous voting rule may provide an incentive for some group members to vote strategically, non-informatively. However, this paper shows that the identity of the best anonymous voting rule does not depend on whether or not they actually choose to do so; a single, second best, rule maximizes utility in both cases.
Keywords: D72; 330; strategic voting; informative voting; committees; imperfect information